IMPROVING PERFORMANCE OF CIVIL SERVANTS: THE EFFECT OF LEADERSHIP, WORK MOTIVATION AND COMPETENCE - Suryani Syamsuddin; Abdul Rahman Kadir; Syamsu Alam (Hasanuddin Journal of Applied Business and Entrepreneurship, 2020)
The optimal performance of civil servants is the target of every state government organization. This aim aims to analyze the influence of leadership style, work motivation and competence both partially and simultaneously on employee performance at the Regional Revenue Service Office of West Sulawesi Province. The research method used is multiple regression analysis to see the effect of independent variables on the dependent variable with the help of SPSS software. The results of this study indicate that leadership has a significant positive effect on employee performance; motivation has a positive and significant effect on performance; Competence hasn’t a significant positive effect on performance. Simultaneously, leadership style, work motivation and competence have a significant positive effect on employee performance.